Застосування теорії оптимального розбиття множин до розв’язання задач штучного інтелекту та розпізнавання образів - Kiseleva, Elena; Prytomanova, Olga; Hart, Liudmyla (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
The paper substantiates the possibility of applying the mathematical theory of continuous problems of optimal partitioning of sets of n-dimensional Euclidean space, which belong to the non-classical problems of infinite-dimensional mathematical programming, to the solution of problems of artificial intelligence and pattern recognition. The problems of pattern recognition both in conditions of certainty and in conditions of uncertainty are formulated. A particular attention is paid to the application of methods of the theory of optimal partitioning for the construction of fuzzy Voronoi diagrams. Examples of constructing fuzzy Voronoi diagrams with the optimal placement of generating points are given.